Effect of altitude on the morphological and sensory characteristics linked to the quality of quelite type chayote fruit (Sechium edule) produced in the Ujarrás Valley, Costa Rica - Rubí Zeledón, Julián (2019)
Quelite type chayote, a local selection, has become the most important in the country, particularly in the main planting and conditioning area in the Ujarrás Valley and in the neighboring plantations located at higher altitudes, towards which the planting areas have been expanding, which could be affecting some morphological and sensory characteristics of the chayote fruit like its uniformity and quality and its acceptance in export markets. The present study aims to determine the effect of altitude on some morphological and sensory characteristics, through laboratory determinations and consultation with local producers. The morphological analysis showed that the low zone presented the highest mean values in the length, width, depth, and weight variables with a significant difference in relation to the high zone; however, the magnitude of the effect does not affect the quality of the export fruit. In the categorical variables (color, shape, distribution of furrows, among others), a greater probability of finding slightly larger cracks in the fruit in the lower zone was found, while for the rest of variables no differences were found. From the sensory point of view, some differences were found in color and firmness; however, for most of the descriptors studied there is no difference as a result of the area.